Between anomy and inhumanity: Femicide cases in the Puno region – Peru - Juan Inquilla Mamani (2020)
In this study, the determining and conditioning factors of the cases of the phenomenon of feminicides that occurred in the last five years in the Puno region were analyzed. The objectives of the study are focused on analyzing and explaining conditioning factors of the phenomenon of feminicide in women and analyzing the motivations and beliefs that a decision of feminicide contains in the family environment. The study method is quantitative in nature, correlational type, the research techniques that have been used are the review of statistical panel data and documentary analysis. The results found allow us to maintain that the phenomenon of feminicide in our environment is related to the symbolic construction of violence by individual, sociodemographic and structural factors, as well as the characterization of the use of this violence as a resource of control and male dominance. Furthermore, it is closely linked to the fight for the recognition of women as subjects of rights and, above all, the human dignity of women.